2015
DOI: 10.1007/s00540-015-2080-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum acidosis prior to reperfusion facilitates hemodynamic recovery following liver transplantation

Abstract: Our findings suggest that less aggressive treatment of acidosis with a slower rate of normalization of serum pH (from low to normal) after reperfusion promotes faster hemodynamic stabilization. These findings provide evidence to support the concept of the pH paradox, and may also substantiate the argument against the usage of alkalizing agents before reperfusion unless acidosis becomes clinically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…After transplantation with excised liver grafts, portal blood is perfused to initiate hepatic function recovery. Although serum pH values normalize slowly after hepatic IR, the heamodynamics stabilize quickly in LT models . Losartan administered to donors and recipients before LT has been found to result in the maintenance of liver function by inhibition of multiple damaging signalling pathways .…”
Section: Pre‐conditions For Lt To Eliminate Cold Hepatic Ir Injurymentioning
confidence: 99%
“…After transplantation with excised liver grafts, portal blood is perfused to initiate hepatic function recovery. Although serum pH values normalize slowly after hepatic IR, the heamodynamics stabilize quickly in LT models . Losartan administered to donors and recipients before LT has been found to result in the maintenance of liver function by inhibition of multiple damaging signalling pathways .…”
Section: Pre‐conditions For Lt To Eliminate Cold Hepatic Ir Injurymentioning
confidence: 99%
“…Cell death in the pH paradox is not oxygen-dependent. Reperfusion at low pH (<6.5) blocks increase of mitochondrial membrane permeability, which allows mitochondrial re-polarization and prevents cell death [ 31 , 32 , 33 ].…”
Section: Impact Of Anesthesia and Surgery (Liver Resection And Liver mentioning
confidence: 99%
“…Whereas the etiological and prognostic effects of acidosis on coagulation and blood transfusion requirements have been extensively described in adults and children submitted to prolonged surgery procedures or trauma, there are few data on the association between acidosis and coagulopathy in OLT. Previous studies suggested that metabolic acidosis may be protective during reperfusion because acidemia suppresses the activity of pH-dependent enzymes, such as proteolytic enzymes and phospholipases, limiting cell damage and tissue necrosis [15,31,32]. Here, we could demonstrate that metabolic acidosis during the reperfusion phase of OLT is directly associated with impaired coagulation and increased need of blood transfusion.…”
Section: Discussionmentioning
confidence: 53%